PENENTUAN KESEPAKATAN DIVERSI TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM PADA PENETAPAN PERKAR NO. 01 / PID.SUS-ANAK / 2017 / PN. CLP - BAUD HERU SETYO (MIH Unsoed, 2019)
Referring to Law no. 16 of 2004 which replaces Law no. 5 of 1991 on the Prosecutor's Office R.I., the Attorney as one of the law enforcement agencies are required to play a more role in upholding the rule of law, protection of public interest, human rights enforcement, and eradication of Corruption, Collusion and Nepotism (KKN). In the new Law of the Prosecutor's Office, the Public Prosecution Service as a state institution exercising state power in the prosecution field must perform its functions, duties and authority independently, irrespective of the influence of the power of government and the influence of other powers (Article 2 paragraph 2 of Law No. 16 Year 2004).In carrying out its duties and authority, the AGO is led by the Attorney General who oversees six Junior Attorneys and 31 High Chief Prosecutors in each province. UU no. Law No. 16 of 2004 on the Attorney of the Republic of Indonesia also suggests that the AGO is in a central position with a strategic role in strengthening the nation's resilience. Because the AGO is in the axis and a filter between the investigation process and the examination process in the court as well as the executor of court decisions and decisions. Thus, the Prosecutor's Office is the controller of the case proceedings (Dominus Litis), since only the Attorney-General's office can determine whether a case may be brought to the Court or not based on valid evidence according to the Criminal Procedure Code.The Cilacap District Attorney Obstacles faced in seeking diversion for child criminal cases with the first obstacle is that most of the criminal acts committed by the threat are more than 7 years imprisonment so that they can not be diversi- fied in accordance with Law Number 11 Year 2012 on Child Criminal Justice System, the second obstacle is the Cilacap State Attorney has 15 (fifteen) prosecutors and only 2 (two) prosecutors have the Decree from the Attorney General and have attended the training as a condition to be prescribed as the Child Procurator and have the right hear the children's case. Of course, with the number of 2 (two) public prosecutors is very less considering the high number of children's case volume in Cilacap District Court, so that prosecutors who do not have a decree are appointed to hear cases of children, the community's assessment that there is no firmness in law enforcement when resolved through diversion. In addition, the community's view of the diversion process tends to be negative which results in the occurrence of resentment and exclusion for children in conflict with the law and the community still wants to retaliate for the perpetrator by imposing penalties or criminal charges, the attitude of the victim's family who assumes a diversionary process will only free the child from responsibility for his deeds